(untitled) (Світ фінансів, 2017)
Заклекта О. І., Ільків В. І. Місцеві податки і збори як джерело наповнення бюджету міста. Здійснено оцінку надходжень місцевих податків і зборів до бюджету міста. Окреслено основні напрямки подальшого реформування інституту місцевих податків і зборів. Zaklekta O., Ilkiv V. Local taxes and tax collections as a source of filling of a city budget. The estimation of receipts of local taxes and tax collections in a city budget is carried out. The basic directions of the further reforming of institute of local taxes and tax collections are outlined.